Analyzing Tensile Testing and Humidity Effects on Polyvinyl Alcohol, Polypyrrole Composites for Strain Sensing - Yunus, Syukri; Rafif, Rifqi; Aulia; Ahmad, Mohammad Hafizi (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2024)
Biocomposite strain sensors must enhance their electrical properties and understand the impact of humidity on these properties. This study aimed to enhance the current density and specific capacitance of polyvinyl alcohol (PVA) and polypyrrole (Ppy) composite materials for strain sensors. The materials were prepared by blending polyvinyl alcohol and polypyrrole, followed by magnetic stirring, drying, and stretching. Current density and specific capacitance measurements were taken before and after the stretching process and at three distinct relative humidity levels (50%, 75%, and 93%). After the tensile test, the results indicated a significant increase in current density by 128.46% and a corresponding rise in specific capacitance by 112.57%. Furthermore, with an increase in relative humidity from 50% to 75%, current density and specific capacitance exhibited remarkable growth of 445.95% and 899.44%, respectively. The subsequent shift from 75% to 93% relative humidity resulted in a comparatively lower percentage increase in current density and specific capacitance at 22.59% and 10.29%, respectively, due to a decrease in hydroxyl bonds. These findings align with the material's characteristic tests, confirming that the improved electrical properties can be attributed to a more uniform distribution of polypyrrole during the stretching process and increased hydroxyl bonds associated with higher humidity levels. As electrical properties increase, the sensor's sensitivity will also rise.